(3QSGdI aj GdJTHjg GdJeKjdis - (3edG NSQh , eMeO Hf aQGehR Hf Ydj,J (B885 (3g` s
(3ChdgG (B:s
(3bO SHb ai HjGf JYQja GdJeKjd HeYfi GdJTHjg GdJeKjdi s
(3BNQgG (B:s
(3hGdMGUd Cf GdJYOO ai GdLedI s
(3Vef eLehY , JQJjHgG (B: (3ef U (B133 - (3U(B138s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B328 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B122s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3eLGejY (B126(3e(B) s
Keywords: (3GdHdGZIs